Ring‐Opening Reaction of Furfural and Tetrahydrofurfuryl Alcohol on Hydrogen‐Predosed Iridium(1 1 1) and Cobalt/Iridium(1 1 1) Surfaces. Issue 9 (23rd March 2017) - Wan, Weiming; Jenness, Glen R.; Xiong, Ke; Vlachos, Dionisios G.; Chen, Jingguang G.
Abstract: The ring‐opening of furfural is crucial for its conversion into value‐added chemicals such as 1, 5‐pentanediol (1, 5‐PeD), an important polymer precursor. Ir‐based catalysts have shown activity in ring‐opening reactions, and the use of an oxophilic metal additive is reported to be beneficial. To better understand the effect of an oxophilic metal on Ir for the opening of the furan ring, a combination of DFT calculations and experimental surface science studies were performed to investigate the ring‐opening of furfural and tetrahydrofurfuryl alcohol. The experimental results suggest that Co/Ir(1 1 1) has a higher ring‐opening activity for an unsaturated furan ring, however, the difference in activities between Ir and Co/Ir(1 1 1) is insignificant for a saturated furan ring. The DFT results reveal that Co/Ir(1 1 1) has a stronger interaction with an unsaturated furan ring than Ir(1 1 1); both surfaces show a weaker interaction with the saturated furan ring, which causes the lower ring‐opening activity than that of furfural. Abstract : Selective surfaces : A study of the mechanism of the ring‐opening reaction on Ir(1 1 1) and Co/Ir(1 1 1) surfaces is presented. Ir(1 1 1) has ring‐opening activity for both furfural and tetrahydrofurfuryl alcohol, and Co/Ir(1 1 1) enhances the ring‐opening of furfural. The interaction between the furan ring and the metal surface determines the activity of the ring‐opening reaction.